RESULTS FROM POST - MARKETING OBSERVATIONAL STUDY FOR THE ASSESSMENT OF SAFETY OF INTRAVENOUS IBANDRONIC ACID IN POSTMENOPAUSAL WOMEN - Markovikj Temelkova, Snezhana; Foteva, Marta; Stojovska Jovanovska, Elizabeta; Stefanovska, Dushica; Bajraktarova Prosheva, Tatjana; Ahmeti, Irfan (SHMSHM - AAMD, 2020)
Our study was non interventional, observational, open, uncontrolled and prospective- retrospective study, multicentre and one branch - during 2009-2011 at secondary and tertiary medical level. 5 medical centres and two clinics from N. Macedonia were included. The study entered 611 pts, but finished 153 pts. 146 were bisphosphonate naive, 7 had previous received peroral bisphosphonate therapy. In our group of patients 36 side effects were registered in 31 patients. 35/36 appeared during first 7 days of application,15/36 did not appeared after first application, 28/36 were with mild intensity and 5 were with moderate intensity and 2 were SAERS. We analyzed review database (2009 to 2011), from the perspective of recent studies. And to point out, that DXA results, together with CMAJ guidelines and FRAX questionnaire, were not changed during last 10 years. Both of them (CMAJ and FRAX), together or without DXA, are solid foundation to begin antiresorbtive bisphosphonate therapy. DXA finding of osteoporosis, sex, and presence of one major or two minor risk factors was the basis of initiating the therapy. All of our patients were female. With the major risk factors 2,1 present in 129 (84%) from 153 patients. In 123 (80,09%) we have registered more than 1 minor risk factors (1,7). Intravenous bisphosphonate therapy, is still most useful steadily in the last decade. It is due to the simple dosing regimens, the adherence, excellent compliance and persistence accurate for certain group of patients. This therapy have few adverse effects.
Keywords: osteoporosis; adverse effects; risk factors